Amyloidosis in major body organs examined during autopsies at Mbarara Regional Referral Hospital - Menya, Jeremy Kirunda; Bruno, Mudde Joseph; Brenda, Musibika Faith; Kizito, Musema; Ibrahim, Gubya; Raymond, Atwine; Abraham, Birungi; Paddy, Behayo; Frank, Ssedyabane (Research square, 2021)
Background Amyloidosis is an infrequent disease that occurs when an abnormal protein, called amyloid, deposits in body organs and disrupts their normal function. Amyloid is not normally found in the body but it can be formed from several different types of protein. Commonly affected organs include the heart, kidneys, gastrointestinal (GI) tract/liver or the peripheral or autonomic nervous system (NS). Amyloidosis can lead to diseases such as Alzheimer’s disease, spongiform encephalopathies and diabetes mellitus type 2. Main objective To establish the prevalence of amyloidosis in major body organs examined during autopsies at Mbarara regional referral hospital and to correlate cause of death with amyloidosis. Methods Brain, heart, kidney, and liver samples were obtained from 23 bodies during autopsies at Mbarara Regional Referral Hospital which were then processed to produce 2 slides per tissue of 2 each of the above organ samples. These slides were then stained using H&E and Congo red staining protocols and then examined for amyloidosis under the light microscope. Results The mean age of the bodies was 61.26 of which 5 (21.7%) were female while 18 (78.3%) were male. 3 bodies (13.0%) tested positive for amyloidosis in the kidney; 2 males (8.70) and 1 female (4.35). All the other organs tested negative. Conclusion In our study, body organ investigation revealed amyloid in the kidney of 3 bodies. The prevalence of amyloidosis was 13% therefore amyloidosis diagnosis ought to be put into consideration at Mbarara Regional Referral
Keywords: Amyloidosis; Autopsies; Organs; Brain; Heart; Kidney; Liver